Reliability and minimal detectable change of the Yoni task for the theory of mind assessment - Isernia, Sara; Cacciatore, Diego Michael; Rossetto, Federica; Ricci, Cristian; Baglio, Francesca (Frontiers in Psychology, 2024)
Introduction The Theory of Mind (ToM) assessment is becoming essential to evaluate the response to a social cognition intervention and to monitor the progression of social abilities impairment in atypical conditions. In the Italian setting, the Yoni task has been recently validated in its short version (the Yoni-48 task) to evaluate ToM in the clinical setting. The present study aimed to verify the test-retest reliability and the Minimal Detectable Change (MDC) of the Yoni-48 task. Methods The Yoni-48 task was administered to 229 healthy adults at two evaluation sessions 3 weeks apart (mean days between sessions = 20.35 ± 1.75) by a psychologist. The test-retest reliability of the Yoni-48 task accuracy and response time was tested by the Intraclass Correlation Coefficient (ICC2,1, two-way random model, absolute agreement type). Then, the MDC95 and MDC90 were computed based on the standard error of measurement. Finally, the 95% limits of agreement were plotted (LOA plot) to visualize the difference and mean score of each pair of measurements. Results The total Yoni-48 task accuracy, but not the response time score, showed a high ICC (>0.80), with an MDC of 0.10. By plotting the LOA plot for the accuracy score no systematic trends were observed. Discussion This evidence will support the adoption of the Yoni task in longitudinal designs.